2009
DOI: 10.1111/j.1749-6632.2009.04549.x
|View full text |Cite
|
Sign up to set email alerts
|

Experience‐induced Malleability in Neural Encoding of Pitch, Timbre, and Timing

Abstract: Speech and music are highly complex signals that have many shared acoustic features. Pitch, Timbre, and Timing can be used as overarching perceptual categories for describing these shared properties. The acoustic cues contributing to these percepts also have distinct subcortical representations which can be selectively enhanced or degraded in different populations. Musically trained subjects are found to have enhanced subcortical representations of pitch, timbre, and timing. The effects of musical experience o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
134
2
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(149 citation statements)
references
References 78 publications
(189 reference statements)
6
134
2
7
Order By: Relevance
“…Contrary to expectations based on higher-level processing, the activation we found was relatively symmetric across hemispheres and covered large regions of Heschl's gyrus; other studies have found limited and more rightlateralized processing of pitch melodies (Zatorre et al, 1994;Griffiths et al, 2001). In studies of auditory perception, pitch and timbre are often treated as separable dimensions (Fletcher, 1934;Kraus et al, 2009;McDermott et al, 2010). However, several studies have also shown that the two can interact (Krumhansl and Iverson, 1992;Warrier and Zatorre, 2002;Russo and Thompson, 2005;Marozeau and de Cheveigné, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to expectations based on higher-level processing, the activation we found was relatively symmetric across hemispheres and covered large regions of Heschl's gyrus; other studies have found limited and more rightlateralized processing of pitch melodies (Zatorre et al, 1994;Griffiths et al, 2001). In studies of auditory perception, pitch and timbre are often treated as separable dimensions (Fletcher, 1934;Kraus et al, 2009;McDermott et al, 2010). However, several studies have also shown that the two can interact (Krumhansl and Iverson, 1992;Warrier and Zatorre, 2002;Russo and Thompson, 2005;Marozeau and de Cheveigné, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Prior investigations into the neurological effects of musical experience have mainly focused on the neural plasticity of the cortex Trainor et al, 2003;Kuriki et al, 2006;Rosenkranz et al, 2007;Lappe et al, 2008), but recent studies have shown that neural plasticity also extends to the subcortical auditory system. This is evidenced by enhanced auditory brainstem response (ABR) phase locking to fundamental pitch and the harmonics of the fundamental and by earlier response latencies in subcortical responses to musical, linguistic, and emotionally valent nonspeech sounds (Musacchia et al, 2007(Musacchia et al, , 2008Wong et al, 2007;Strait et al, 2009) (for review, see Kraus et al, 2009). Because playing an instrument and listening to music involves both high cognitive demands and auditory acuity, these subcortical enhancements may result from corticofugal (topdown) mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Also, we are aware of the welldocumented beneficial effects of music [5], and that it is possible to train one's hearing to recover sensory abilities and thus music appreciation (e.g. [3,4]). Recently we conducted an experiment using an audio-based computer game called the "Music Puzzle", and preliminary results have been reported in [2].…”
Section: Introductionmentioning
confidence: 99%